Biological monitoring of workers exposed to acetone in acetate fibre plants. Issue 9 (September 1992) - Fujino, A; Satoh, T; Takebayashi, T; Nakashima, H; Sakurai, H; Higashi, T; Matumura, H; Minaguchi, H; Kawai, T
Abstract : Concentrations of acetone in urine, alveolar air, and blood were measured by gas chromatography with flame ionisation detection for 110 subjects occupationally exposed to acetone (mean 372 ppm) in three factories. Significant relations were found between the time weighted average environmental concentration and the concentration in the biological samples. The strongest correlation was between the concentration of acetone in urine and the degree of exposure (r = 0.71, 95% CI 0.64-0.77). This suggests that urinary acetone concentration is the best biological index of occupational exposure to acetone.